Literacy-as-event: accounting for relationality in literacy research. Issue 1 (2nd January 2020) - Burnett, Cathy; Merchant, Guy
ABSTRACT: Research in New Literacy Studies has demonstrated how literacy consists of multiple socially and culturally situated practices illuminated through a focus on literacy events. Recently, this sociocultural perspective has been complemented by relational thinking that views literacy as an ongoing reassembling of the human and more-than-human. This conceptual article proposes that, in exploring how relational thinking might be deployed in literacy research and practice, it is helpful to revisit conceptualisations of literacy events. Specifically it proposes the notion of 'literacy-as-event' as a heuristic for thinking with the fluid and elusive nature of meaning-making, elaborating on three propositions: (1) event is generated as people and things come into relation; (2) what happens always exceeds what can be conceived and perceived; and (3) implicit in the event are multiple potentialities. Approaching literacy research through engaging with literacy-as-event promotes an expansive, reflective, and imaginative engagement with literacy practices that aligns with relational thinking.